Mechanisms For the Development of a National Worldview Using Modern Educational Technologies - Hurshida Abduhalilovna Kadirova (Academia One Publishing, 2023)
the article reflected on the mechanisms of increasing the activity of educational consumers on the basis of a national-humanitarian approach and developing a national worldview on the basis of their appropriation.
Keywords: national-humanitarian approach; organization in an educational environment